Intraocular pressure variation in pregnancy: a prospective study - Sundaram, Lalith; Swaminathan, Sruthi; TC, Ranjakumar; Ashraf, Rahana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To detect Intra Ocular Pressure (IOP) in each trimester of pregnancy and evaluate difference in measurement of intraocular pressure in each trimester of pregnancy. Methods: 100 healthy pregnant women within age group ranging from 21 to 35 years were included in the study. Intra ocular pressures (Goldmann-Applanation Tonometer) were calculated at 3 time periods: First trimester, Second trimester, Third trimester. Informed consent was taken from all patients. Patients had no systemic or ocular co-morbidities. All of the patients underwent comprehensive ophthalmologic examinations, including Refraction, Intraocular pressure (IOP), Anterior segment and Fundus examination. Results: The mean age was 25 years in the study group. The mean IOP in the second trimester of pregnancy was measured to be reduced than first trimester by 9.33% &20.33% by third trimester in right eye & decrease of 14.2% in second trimester and 28.84% in third trimester left eye. The results are statistically significant confirmed by ANOVA. Conclusions: Changes during pregnancy causes variation in IOP which is observed in pregnant women resulting from increased water retention during pregnancy. Monitoring of IOP during pregnancy is also important in management of glaucoma patients and their medication. Most of the changes are reversible and resolved in the postpartum period or after cessation of breastfeeding. Awareness of the changes during pregnancy and routine screening during antenatal period should be improvised.